2021
DOI: 10.3389/fimmu.2021.747594
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Complement Pathway Inhibition Does Not Abrogate Meningococcal Killing by Serum of Vaccinated Individuals

Abstract: Dysregulation of complement activation causes a number of diseases, including paroxysmal nocturnal hemoglobinuria and atypical hemolytic uremic syndrome. These conditions can be treated with monoclonal antibodies (mAbs) that bind to the complement component C5 and prevent formation of the membrane attack complex (MAC). While MAC is involved in uncontrolled lysis of erythrocytes in these patients, it is also required for serum bactericidal activity (SBA), i.e. clearance of encapsulated bacteria. Therefore, term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…It also blocks the amplification of classical and lectin pathway-dependent–C5 activation, although it does not impact amplification-independent complement activation via these pathways, which may potentially lead to lower infection risk in vaccinated patients as compared with other proximal complement inhibitors. 1, 16, 22, 23 Based on data from nonclinical and phase 1 studies, the pharmacokinetics of iptacopan is characterized by high absorption and moderate clearance (data on file). The main clearance pathway is hepatic metabolism (cytochrome P450 2C8-mediated oxidation, direct glucuronidation), followed by direct renal excretion (∼25%).…”
Section: Discussionmentioning
confidence: 99%
“…It also blocks the amplification of classical and lectin pathway-dependent–C5 activation, although it does not impact amplification-independent complement activation via these pathways, which may potentially lead to lower infection risk in vaccinated patients as compared with other proximal complement inhibitors. 1, 16, 22, 23 Based on data from nonclinical and phase 1 studies, the pharmacokinetics of iptacopan is characterized by high absorption and moderate clearance (data on file). The main clearance pathway is hepatic metabolism (cytochrome P450 2C8-mediated oxidation, direct glucuronidation), followed by direct renal excretion (∼25%).…”
Section: Discussionmentioning
confidence: 99%
“…This may be important in immunized individuals such that membrane attack complex-dependent killing of bacteria, such as Neisseria meningitidis, is maintained. 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, iptacopan, does not fully block the generation of MAC initiated by the C5 convertases of the classical and lectin pathways (C4b2aC3b) and therefore infection risk is theoretically lower. This may be important in immunized individuals such that MAC-dependent killing of bacteria, such as Neisseria meningitidis, is maintained [27][28][29] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Serum bactericidal titers were measured as previously described ( 34 ), but with modifications. Each reaction mixture contained approximately 400 CFUs of mid-log phase Hib bacteria and 20% human serum with internal complement preserved ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…Neisseria meningitidis infections dominate ( 31 , 32 ), but it is recommended that children treated with eculizumab also receive vaccinations to prevent Streptococcus pneumoniae and Hib infections. As potential alternatives to C3 and C5 inhibitors, AP inhibitors are being developed and we have previously shown that AP inhibition abrogates meningococcal SBA and pneumococcal opsonophagocytosis in vaccine-naïve, but not in vaccinated individuals ( 33 , 34 ). Here we assessed the impact of complement inhibitors targeting C3, the AP (fB, fD), the lectin pathway (LP) (MASP-2) and the terminal pathway (C5) on both SBA and opsonophagocytic killing of Hib isolates by serum or reconstituted blood from individuals before and after vaccination with a capsule conjugate vaccine.…”
Section: Introductionmentioning
confidence: 99%